2019
DOI: 10.1111/anec.12705
|View full text |Cite
|
Sign up to set email alerts
|

Associations between QT interval subcomponents, HIV serostatus, and inflammation

Abstract: Background The total QT interval comprises both ventricular depolarization and repolarization currents. Understanding how HIV serostatus and other risk factors influence specific QT interval subcomponents could improve our mechanistic understanding of arrhythmias. Methods Twelve‐lead electrocardiograms (ECGs) were acquired in 774 HIV‐infected (HIV+) and 652 HIV‐uninfected (HIV−) men from the Multicenter AIDS Cohort Study. Individual QT subcomponent intervals were analyzed: R‐onset to R‐peak, R‐peak to R‐end, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
0
16
0
3
Order By: Relevance
“…Notably, in the present analysis, the absolute change in QTc associated with T‐use was larger than that associated with HIV seropositivity. Given the association of longer QTc with HIV infection and the increased prevalence of hypogonadism and low T‐levels in MLWH [4–5,14], the shorter QTc associated with T‐use observed in this study might support a protective effect on ventricular repolarization that could counteract the potentially deleterious prolongation seen with HIV infection. In light of our findings, QTc duration data may be helpful when evaluating initiation and discontinuation of T‐use, particularly in MLWH without cardiovascular disease and those taking QTc‐prolonging medications.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Notably, in the present analysis, the absolute change in QTc associated with T‐use was larger than that associated with HIV seropositivity. Given the association of longer QTc with HIV infection and the increased prevalence of hypogonadism and low T‐levels in MLWH [4–5,14], the shorter QTc associated with T‐use observed in this study might support a protective effect on ventricular repolarization that could counteract the potentially deleterious prolongation seen with HIV infection. In light of our findings, QTc duration data may be helpful when evaluating initiation and discontinuation of T‐use, particularly in MLWH without cardiovascular disease and those taking QTc‐prolonging medications.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings demonstrate that T‐use is associated with shorter electrocardiographic QTc duration independent of HIV serostatus. This finding may be particularly relevant for MLWH, as MLWH are less likely to discontinue testosterone and more likely to have QT prolongation associated with HIV infection [5,16]. Longer QTc duration has been associated with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that increase in cytokines, such as IL-6, may prolong QT in patients with viral infection. HIV-associated inflammation, causing elevated IL-6, has been shown to be independently associated with QT prolongation [ 80 ] and prolonged repolarization represented as T wave onset-to-peak duration [ 81 ]. HIV-positive patients had longer QTc intervals and QTc prolongation often > 500 ms, even after taking into account other QT prolonging drugs like methadone when compared to HIV negative patients [ 82 ].…”
Section: Monitoring Of Corrected Qt Interval (Qtc)mentioning
confidence: 99%